2004
DOI: 10.1002/humu.20025
|View full text |Cite
|
Sign up to set email alerts
|

Human vitamin K-dependentGAS6: Gene structure, allelic variation, and association with stroke

Abstract: The product of the growth arrest-specific gene 6 (GAS6), a ligand for the Axl, Sky, and Mer tyrosine kinase receptors, is a vitamin K-dependent protein, structurally related to anticoagulant protein S. Gas6-deficient mice are protected against thrombosis, demonstrating the importance of this protein in the cardiovascular system. The present study was aimed at determining the human GAS6 intron-exon structure and analyzing the gene for the presence of allelic variants that could be associated with atherothrombot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 30 publications
0
57
0
Order By: Relevance
“…Because vessel wall response to injury is a major component of human atherothrombotic pathology, Gas6 could be a key player in the pathophysiology of cardiovascular diseases. Consistent with this theory, Munoz et al (8 ) have shown that a polymorphism of the GAS6 gene was associated with stroke. Therefore, lower plasma Gas6 concentrations could result in higher sensitivity to vascular injury, with plaque fibrous cap thinning, vascular smooth muscle cell and endothelium apoptosis; and, thus, a higher susceptibility to plaque rupture or erosion.…”
Section: Discussionmentioning
confidence: 81%
“…Because vessel wall response to injury is a major component of human atherothrombotic pathology, Gas6 could be a key player in the pathophysiology of cardiovascular diseases. Consistent with this theory, Munoz et al (8 ) have shown that a polymorphism of the GAS6 gene was associated with stroke. Therefore, lower plasma Gas6 concentrations could result in higher sensitivity to vascular injury, with plaque fibrous cap thinning, vascular smooth muscle cell and endothelium apoptosis; and, thus, a higher susceptibility to plaque rupture or erosion.…”
Section: Discussionmentioning
confidence: 81%
“…54 Still, Gas6 levels in plasma were higher in patients with venous thromboembolic disease as compared with healthy volunteers. 55 Also, genetic evidence shows an association between certain single nucleotide polymorphisms in the GAS6 gene and stroke, 56 making involvement of TAM receptor in human, and not only murine, hemostasis likely.…”
Section: Tam Receptorsmentioning
confidence: 99%
“…Conversely, abnormal activation of the Gas6 pathway might also contribute to disease phenotypes due to platelet activation (e.g., heparin-induced thrombocytopenia, anti-phospholipid antibody syndrome) that are characterized by thrombosis. A very recent study indicates a significant association between a Gas6 polymorphism and ischemic stroke, placing Gas6 as a promising candidate for a susceptibility gene for this disease (45).…”
Section: Figure 11mentioning
confidence: 99%